Study on the Protective Effect of Naringin-Regulated LncRNA GAS5 against Mitochondrial Apoptosis in Osteoarthritic Chondrocytes - LIN Qin; ZHU Yingkai; LIN Yanming; LAN Shujie; CHEN Changxing; FU Changlong (康复学报, 2025)
ObjectiveTo explore the mechanism by which naringin inhibits mitochondrial apoptosis in chondrocytes and improves osteoarthritis (OA) based on lncRNA GAS5.MethodsThrough in vivo experiments, thirty 2-month-old male Sprague-Dawley (SD) rats were selected and randomly divided into sham operation group, model group and a naringin group by random number method, with 10 rats in each group. The model and naringin groups were used to construct the OA rat model by the modified Hulth method. Rats in sham operation group were only opened at the same position, and the wound was sutured immediately. Four weeks after the operation, the naringin group was given 75 mg/kg naringin solution by intragastric administration, while the sham operation and model groups were given the same amount of normal saline. Intragastric administration was conducted 6 times a week for 4 consecutive weeks. The morphological changes in the pathological sections of articular cartilage tissue were analyzed and observed by toluidine blue and Safranin O staining. The expression level of lncRNA GAS5 and the protein expression levels of Caspase-3, Bax, MMP-13 and Cyt-C in the articular cartilage tissues of rats were detected by qPCR and Western blot. The effect of naringin on the chondrocytes apoptosis in rat cartilage tissue was detected by TUNEL method. For in vitro experiments: (1) The cells were randomly divided into four groups: blank control group, SNP group, naringin group and SNP+naringin group. The expression level of lncRNA GAS5 in each group was detected by fluorescence in situ hybridization (FISH) method. (2) The cells were randomly divided into four groups: blank+sh-NC group, SNP+sh-NC group, blank+sh-GAS5 group and SNP+sh-GAS5 group. The expression level of lncRNA GAS5 in each group was detected by qPCR. (3) The cells were randomly divided into four groups: blank control group, SNP+naringin group, SNP group and the SNP+naringin+sh-GAS5 group. The protein expression levels of Caspase-3, Bax, MMP-13 and Cyt-C in each group were detected by Western blot.Results(1) In vivo experimental results: The toluidine blue and Safranin O staining showed that the knee articular cartilage in the sham operation group presented a clear hierarchical structure, with a smooth and intact surface. The chondrocytes were neatly and orderly arranged, and the tidal line was clearly visible. The surface of the cartilage layer of the knee joint in the model group was rough and uneven, with obvious defects. The structure became blurred and cavities could be seen. Compared with the model group, the cartilage surface in the naringin group was relatively smooth, the chondrocytes were arranged more neatly, the tidal line remained intact, and the cartilage staining presented a more uniform state. The results of qPCR showed that, compared with the sham operation group, the expression level of lncRNA GAS5 in the model group was higher (P<0.05). Compared with the model group, the expression level of lncRNA GAS5 in the naringin group decreased more (P<0.05). Western blot results showed that, compared with the sham operation group, the protein expression levels of Caspase-3, Bax, MMP-13 and Cyt-C in the model group increased more significantly (P<0.05). Compared with the model group, the protein expression levels of Caspase-3, Bax, MMP-13 and Cyt-C in the naringin group decreased more significantly (P<0.05). The results of TUNEL method showed that, compared with the sham operation group, the chondrocytes apoptosis rate in the model group increased more significantly (P<0.05). Compared with the model group, the chondrocytes apoptosis rate in the naringin group decreased more significantly (P<0.05). (2) In vitro experimental results: The FISH results showed that, compared with the blank control group, the fluorescence expression level of lncRNA GAS5 in chondrocytes of the SNP group increased more significantly (P<0.05). Compared with the SNP group, the fluorescence expression level of lncRNA GAS5 in the SNP+naringin group decreased more significantly (P<0.05). The results of qPCR showed that, compared with the blank+sh-NC group, the expression level of lncRNA GAS5 mRNA in the SNP+sh-NC group increased more significantly (P<0.05). Compared with the blank+sh-NC group, the lncRNA GAS5 mRNA level in the blank+sh-GAS5 group decreased more significantly (P<0.05), indicating the successful transfection of sh-GAS5. Compared with the SNP+sh-NC group, the relative expression level of lncRNA GAS5 mRNA in the SNP+sh-GAS5 group decreased more significantly (P<0.05). Western blot results showed that, compared with the blank control group, the protein expression levels of Caspase-3, Bax, MMP-13 and Cyt-C in the SNP group increased more significantly (P<0.05). Compared with the SNP group, the protein expression levels of Caspase-3, Bax, MMP-13 and Cyt-C in the SNP+naringin group decreased more significantly (P<0.05). Compared with the SNP+naringin group, the protein expression levels of Caspase-3, Bax, MMP-13 and Cyt-C in the SNP+naringin+sh-GAS5 group increased more significantly (P<0.05).ConclusionNaringin can improve OA by inhibiting the expression of ncRNA GAS5, reducing mitochondrial apoptosis in chondrocytes, and delaying the process of cartilage degeneration.